Antimicrobial and antioxidant activity of Pistia stratiotes (L.) - TULIKA TYAGI,; PUNEET PARASHAR, (International Journal of Pharma and Bio Sciences, 2017)
The present study was designed to evaluate the antioxidant and antimicrobial activity of various extracts of P. stratiotes. Antioxidant Activity is done by in vitro DPPH (2,2-diphenyl-1- picryl hydrazyl) using spectrophotometric method. Antimicrobial Activity is done by by well diffusion method and MIC (Minimum Inhibitory Concentration) using plate method. The methanolic extracts of P. stratiotes roots showed an IC50 values of 4.098±0.03 mg/ml highest antioxidant activity whereas leaves show IC50 values of 2.463±0.018 mg/ml of minimum activity in DPPH method. When assayed for Antibacterial activity leaves extract at 160 mg/ml produced zone of inhibition of 9.00 ± 0.817 against E. coli organism, 8.00±0.00 against S. aureus organism, 8.33± 0.47 against P. aeruginosa organism and 9.33± 0.47 against B. subtilis organism. While root extract at 160 mg/ml against S. aureus, P. aeruginosa, B. subtilis show zone of inhibition of 9.67± 0.47 mg/ml, 8.67 ± 0.47mg/ml and 8.33± 0.47mg/ml respectively. Antifungal activity for C. albicans and A. niger at 300 mg/ml for leave extract produce zone of inhibition of 10.00±0.00 mg/ml and 9.67±0.47 mg/ml while for root extract produce zone of inhibition of 8.33±0.47 mg/ml and 9.66±0.47mg/ml respectively. The result of this study reveals that Pistia stratiotes could be considered as potential source of natural antioxidant and antimicrobial plant for an alternative topical choice in the treatment of infections.